Reactions in American print media to Adamic’s book The Native’s Return - Klemenčič, Matjaž; Mrđenović, Milan (Slavia Centralis, 2022)
The article presents a description of the reactions to Adamic’s book The Native’s Return in the American newspapers. The book was published in February 1934 in many copies; several reprints followed. The book is the result of Adamic’s visit to Yugoslavia as a Guggenheim Fellow in 1932 and 1933. After the assassination of the Yugoslav King Aleksandar on October9, 1934, the book was a must-read for Americans interested in the situation in the then Yugoslavia. The authors outlined some positive reviews, which were published in leading American newspapers and magazines. They recommended the book to the readers for its good English, as well as content. In addition to the positive reviews, the authors also described some negative reactions which did not harm Adamic’s book, but promoted it further.
Keywords: Louis Adamič; American literature; Yugoslavia; USA; Nikola Tesla